PENGARUH KUALITAS PRODUK, GAYA HIDUP DAN WORD OF MOUTH PADA KEPUTUSAN PEMBELIAN IPHONE DI BEKASI TIMUR - Ashraff Rizky Setyawan; Milda Handayani; Rini Wijayaningsih (Draf Solusi Indonesia, 2025)
This study aims to analyze the influence of product quality, lifestyle and word of mouth on iPhone Purchasing Decisions. This study uses a quantitative method with an explanatory approach and a cross-sectional research design. The research sample consists of the number of respondents selected using the Accidental sampling technique. The research instrument is a questionnaire that has been tested for validity and reliability. Data analysis was carried out using the Partial Least Squares (PLS) method with the help of SmartPLS 3 software. The results of the study show that: 1) product quality has a significant effect on purchasing decisions, 2) lifestyle has a significant effect on purchasing decisions, 3) word of mouth has a significant effect on purchasing decisions